2008
DOI: 10.1152/ajpcell.00042.2008
|View full text |Cite
|
Sign up to set email alerts
|

Neurokinin A engages neurokinin-1 receptor to induce NF-κB-dependent gene expression in murine macrophages: implications of ERK1/2 and PI 3-kinase/Akt pathways

Abstract: Sun J, Ramnath RD, Tamizhselvi R, Bhatia M. Neurokinin A engages neurokinin-1 receptor to induce NF-B-dependent gene expression in murine macrophages: implications of ERK1/2 and PI 3-kinase/Akt pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
2
24
1
Order By: Relevance
“…In this respect, Sun et al (2008) describe the upregulation of chemokine and cytokine receptor expression by SP in neutrophils, an effect involving NK-1R and the activation of NF-jB. These findings, in accordance with ours, suggest and that SP is related to chronic inflammation with regulation of the production of LTB 4 .…”
Section: Discussionsupporting
confidence: 89%
“…In this respect, Sun et al (2008) describe the upregulation of chemokine and cytokine receptor expression by SP in neutrophils, an effect involving NK-1R and the activation of NF-jB. These findings, in accordance with ours, suggest and that SP is related to chronic inflammation with regulation of the production of LTB 4 .…”
Section: Discussionsupporting
confidence: 89%
“…The findings strongly suggest that the SP-NK1R-signaling cascade contributes to type 1 immunity, as well as inflammatory responses. Although NK1R is ubiquitously expressed in addition to the CNS, it was demonstrated that NK2R is mostly expressed in peripheral tissues (29)(30)(31)(32)(33). Although the precise function of the NKA-NK2R-signaling pathway, especially in immune responses, is less-well known compared with that of NK1R, we demonstrated in this study that NK2R-mediated NKA stimulation enhances DC function, such as IFN-a/b production (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Although the tachykinins were initially considered neurotransmitters, many articles reported that expression of their receptors, NK1R and NK2R, was observed in nonneural tissues, including endothelial cells, fibroblasts, smooth muscle cells, and inflammatory cells, suggesting that tachykinins function between the nervous system and other organs (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of NF-κB is also regulated by upstream signaling proteins including MAPKs (ERK, JNK, and p38 MAPK) and Akt, those are groups of signaling molecules to play pivotal roles in NF-κB activation [13,27]. MAPKs are involved in pro-inflammatory signaling cascades and regulate the activation of NF-κB in LPS-stimulated immune cells [2,3,25].…”
Section: Discussionmentioning
confidence: 99%